Multi-step water quality forecasting using a boosting ensemble multi-wavelet extreme learning machine model - Barzegar, Rahim; Asghari Moghaddam, Asghar; Adamowski, Jan; Ozga-Zielinski, Bogdan (Stochastic Environmental Research and Risk Assessment, 2018)

Strategies for integrating water management and spatial planning: Organising for spatial quality in the Dutch “Room for the River” program - Busscher, T.; Van Den Brink, M.; Verweij, S. (Journal of Flood Risk Management, 2019)
In response to extreme flood events and an increasing awareness that traditional flood control measures alone are inadequate to deal with growing flood risks, spatial flood risk management strategies have been introduced. These strategies do not only aim to reduce the probability and consequences of floods, they also aim to improve local and regional spatial qualities. To date, however, research has been largely ignorant as to how spatial quality, as part of spatial flood risk management strategies, can be successfully achieved in practice. Therefore, this research aims to illuminate how spatial quality is achieved in planning practice. This is done by evaluating the configurations of policy instruments that have been applied in the Dutch Room for the River policy program to successfully achieve spatial quality. This policy program is well known for its dual objective of accommodating higher flood levels as well as improving the spatial quality of the riverine areas. Based on a qualitative comparative analysis, we identified three successful configurations of policy instruments. These constitute three distinct management strategies: the “program‐as‐guardian”, the “project‐as‐driver,” and “going all‐in” strategies. These strategies provide important leads in furthering the development and implementation of spatial flood risk management, both in the Netherlands and abroad.
Keywords: Ouvrage_Collectif_Numéro1

Bloated bodies and broken bricks: Power, ecology, and inequality in the political economy of natural disaster recovery - Sovacool, Benjamin K.; Tan-Mullins, May; Abrahamse, Wokje (World Development, 2018)

Flood Risk Management: Exploring the Impacts of the Community Rating System Program on Poverty and Income Inequality - Noonan, Douglas S.; Sadiq, Abdul‐Akeem A. (Risk Analysis, 2018)
Abstract Flooding remains a major problem for the United States, causing numerous deaths and damaging countless properties. To reduce the impact of flooding on communities, the U.S. government established the Community Rating System (CRS) in 1990 to reduce flood damages by incentivizing communities to engage in flood risk management initiatives that surpass those required by the National Flood Insurance Program. In return, communities enjoy discounted flood insurance premiums. Despite the fact that the CRS raises concerns about the potential for unevenly distributed impacts across different income groups, no study has examined the equity implications of the CRS. This study thus investigates the possibility of unintended consequences of the CRS by answering the question: What is the effect of the CRS on poverty and income inequality? Understanding the impacts of the CRS on poverty and income inequality is useful in fully assessing the unintended consequences of the CRS. The study estimates four fixed‐effects regression models using a panel data set of neighborhood‐level observations from 1970 to 2010. The results indicate that median incomes are lower in CRS communities, but rise in floodplains. Also, the CRS attracts poor residents, but relocates them away from floodplains. Additionally, the CRS attracts top earners, including in floodplains. Finally, the CRS encourages income inequality, but discourages income inequality in floodplains. A better understanding of these unintended consequences of the CRS on poverty and income inequality can help to improve the design and performance of the CRS and, ultimately, increase community resilience to flood disasters.

Guide to identifying alert thresholds for heat waves in Canada based on evidence - Gachon, P.; Bussières, Louise; Gosselin, P.; Raphoz, M.; Bustinza, R.; Martin, Philippe H.; Dueymes, G.; Gosselin, Denis; Labrecque, Sylvain; Jeffers, S.; Yagouti, Abderrahmane (2016)
Among natural-disaster risks, heat waves are responsible for a large number of deaths, diseases and economic losses around the world. As they will increase in severity, duration and frequency over the decades to come within the context of climate change, these extreme events constitute a genuine danger to human health, and heat-warning systems are strongly recommended by public health authorities to reduce this risk of diseases and of excessive mortality and morbidity. Thus, evidence-based public alerting criteria are needed to reduce impacts on human health before and during persistent hot weather conditions. The goal of this guide is to identify alert thresholds for heat waves in Canada based on evidence, and to propose an approach for better defining heat waves in the Canadian context in order to reduce the risks to human health and contribute to the well-being of Canadians. This guide is the result of the collaboration among various research and public institutions working on: 1) meteorological and climate aspects, i.e. the Meteorological Service of Canada (MSC, Environment and Climate Change Canada), and the ESCER centre at the Universite du Quebec a Montreal, and 2) public health, i.e. Health Canada and the Institut National de Sante Publique du Quebec.
Keywords: Gachon_Philippe

Instruments for Strategies to Face Floods through Prevention, Mitigation, and Preparation in Europe: The Age of Alignment - Gralepois, Mathilde (Facing Hydrometeorological Extreme Events, 2019)
Keywords: Ouvrage_Collectif_Numéro1

Les impacts des changements climatiques sur la santé au Québec : l’exemple de l’Estrie - Petit, Geneviève; Lachance, Éric; Généreux, Mélissa; Barbeau-Meunier, Charles-Antoine; Pinsonneault, Linda; Dao, Huy Hao; Milot, Marie-Christine; Baron, Geneviève; Carignan, Alex (Université de Sherbrooke, 2019)
L’Organisation mondiale de la Santé (OMS) soutient que les changements climatiques représentent la plus grande menace pour la santé dans le monde au 21e siècle. Ceux-ci influencent négativement plusieurs déterminants sociaux et environnementaux de la santé comme l’accessibilité à la nourriture et la qualité de cette dernière, l’eau et l’air. Blessures, impacts psychosociaux, aggravation de maladies respiratoires, malnutrition, maladies infectieuses, décès : les conséquences sanitaires sont susceptibles d’affecter les populations sur tous les continents. Le Canada se réchauffe deux fois plus rapidement que la moyenne mondiale en raison de sa proximité au pôle Arctique, où le réchauffement est accéléré comparativement à l’équateur (Bush et Lemmen, 2019). Ainsi, le Québec n’est certainement pas à l’abri des changements climatiques. Dans le Sud de la province, les températures moyennes observées ont augmenté de plus d’un degré depuis 1970 et des répercussions se font déjà sentir dans notre environnement. Ce réchauffement, accompagné d’une plus grande variabilité du climat (augmentation du risque d’orages, de tempêtes et d’extrêmes hydrométéorologiques en général), représente un défi grandissant pour les professionnel.le.s de la santé. Dans la région de l’Estrie, les professionnel.le.s de santé publique ont effectué une analyse qui leur ont permis d’identifier quatre principaux problèmes environnementaux associés aux changements climatiques, soit : les vagues de chaleur; les inondations; les tiques à pattes noires; le pollen de l’herbe à poux. Ces problèmes ont des impacts importants sur la santé, c’est-à-dire potentiellement graves ou qui touchent un grand nombre de personnes. Le stress et les pertes (humaines et matérielles) engendrées par ces différents problèmes environnementaux peuvent aussi représenter une source majeure de problèmes psychologiques significatifs pouvant persister dans le temps. De plus, ces impacts sont variables selon les différents contextes sociaux des individus et des communautés, générant des inégalités sociales de santé.
Keywords: Généreux_Mélissa

Impacts psychosociaux négatifs des vagues de chaleur, des inondations, des feux de forêt et des tempêtes chez les travailleurs du Québec. - Adam-Poupart, A; Pouliot, L; Deger, L; Sassine, M.P; Coll, E.T (Institut national de santé publique du Québec (INSPQ), 2019)
Dans le cadre de la mise en œuvre du Plan d’action 2013-2020 sur les changements climatiques du Québec, le ministère de la Santé et des Services sociaux du Québec a mandaté l’Institut national de santé publique du Québec afin de mener une étude exploratoire portant sur les impacts psychosociaux vécus chez les travailleurs à la suite de quatre événements météorologiques extrêmes qui s’accentueront avec les changements climatiques, soit les vagues de chaleur, les inondations, les tempêtes et les feux de forêt. Cette étude exploratoire visait à examiner brièvement la littérature et les connaissances de différents acteurs-clés afin de proposer par la suite des projets de recherche plus importants et qui répondent aux besoins et aux enjeux des milieux de travail et de la santé publique au Québec. Elle a mis en évidence que les événements météorologiques extrêmes étudiés peuvent entraîner des impacts psychosociaux chez les travailleurs, mais les connaissances sur ces impacts varient grandement selon l’événement. Les impacts psychosociaux chez les travailleurs ont été plus documentés dans la littérature scientifique pour les tempêtes et l’ont été de façon moins importante pour les inondations et les feux de forêt et négligeable pour les vagues de chaleur. Les travailleurs des services de la première ligne (comme les intervenants municipaux, les policiers, les pompiers, et les professionnels de la santé qui interviennent auprès des sinistrés, le personnel des services de travaux publics, etc.) et les agriculteurs font partie des populations de travailleurs qui ont été les plus étudiées. Les impacts psychologiques négatifs comme de l’épuisement, de la fatigue, de la détresse psychologique, de l’anxiété, de la colère et de la tristesse ont été plus souvent rapportés dans la littérature que les impacts sociaux. Il existe des facteurs de risque organisationnels (ex. : surcharge de travail, le manque de formation, de ressources matérielles, de personnels disponibles) et personnels (ex. : le fait d’être sinistré, le manque de contact avec les membres de la famille), communs à plusieurs événements et types de travailleurs, et qui peuvent aggraver les impacts psychosociaux vécus chez les travailleurs. Il existe aussi des facteurs de protection (ex. : reconnaissance ou gratitude, résilience individuelle, soutien social et efficacité collective). Il est important de consulter des acteurs clés pour bonifier les connaissances de la littérature scientifique. Dans le cadre de cette étude, les consultations avec des acteurs clés ont permis d’identifier de nouveaux travailleurs vulnérables, d’en apprendre davantage sur les caractéristiques de certains événements météorologiques extrêmes et de réaliser que les impacts psychosociaux vécus à la suite de ceux-ci pouvaient être positifs. L’acquisition de connaissances sur les impacts psychosociaux vécus chez les travailleurs à la suite des inondations est un des sujets qui répond aux besoins et aux enjeux des milieux de travail et de la santé publique au Québec.

Economic inequality and institutional adaptation in response to flood hazards: a historical analysis - Van Bavel, Bas; Curtis, Daniel R.; Soens, Tim (Ecology and Society, 2018)

On the relation between weather-related disaster impacts, vulnerability and climate change - Visser, Hans; Petersen, Arthur C.; Ligtvoet, Willem (Climatic Change, 2014)
Disasters such as floods, storms, heatwaves and droughts can have enormous implications for health, the environment and economic development. In this article, we address the question of how climate change might have influenced the impact of weather-related disasters. This relation is not straightforward, since disaster burden is not influenced by weather and climate events alone—other drivers are growth in population and wealth, and changes in vulnerability. We normalized disaster impacts, analyzed trends in the data and compared them with trends in extreme weather and climate events and vulnerability, following a 3 by 4 by 3 set-up, with three disaster burden categories, four regions and three extreme weather event categories. The trends in normalized disaster impacts show large differences between regions and weather event categories. Despite these variations, our overall conclusion is that the increasing exposure of people and economic assets is the major cause of increasing trends in disaster impacts. This holds for long-term trends in economic losses as well as the number of people affected. We also found similar, though more qualitative, results for the number of people killed; in all three cases, the role played by climate change cannot be excluded. Furthermore, we found that trends in historic vulnerability tend to be stable over time, despite adaptation measures taken by countries. Based on these findings, we derived disaster impact projections for the coming decades. We argue that projections beyond 2030 are too uncertain, not only due to unknown changes in vulnerability, but also due to increasing non-stationarities in normalization relations.

Flood risk, vulnerability and environmental justice: Evidence and evaluation of inequality in a UK context - Walker, Gordon; Burningham, Kate (Critical Social Policy, 2011)
Flooding has only relatively recently been considered as an environmental justice issue. In this paper we focus on flooding as a distinct form of environmental risk and examine some of the key evidence and analysis that is needed to underpin an environmental justice framing of flood risk and flood impacts. We review and examine the UK situation and the body of existing research literature on flooding to fill out our understanding of the patterns of social inequality that exist in relation to both flood risk exposure and vulnerability to the diverse impacts of flooding. We then consider the various ways in which judgements might be made about the injustice or justice of these inequalities and the ways in which they are being sustained or responded to by current flood policy and practice. We conclude that there is both evidence of significant inequalities and grounds on which claims of injustice might be made, but that further work is needed to investigate each of these. The case for pursuing the framing of flooding as an environmental justice issue is also made.

Mapping the vulnerability hotspots over Hindu-Kush Himalaya region to flooding disasters - Elalem, Shada; Pal, Indrani (Weather and climate extremes, 2015)
Abstract A disproportionate share of the global economic and human losses caused by environmental shocks is borne by people in the developing nations. The mountain region of Hindu-Kush Himalaya (HKH) in South Asia is threatened by numerous flooding events annually. An efficient disaster risk reduction often needs to rest upon location-based synoptic view of vulnerability. Resolving this deficit improves the ability to take risk reduction measures in a cost-effective way, and in doing so, strengthens the resilience of societies to flooding disasters. The central aim of this research is to identify the vulnerable locations across HKH boundary from the perspective of reported history of economic and human impacts due to occurrence of flooding disasters. A detailed analysis indicates a very high spatial heterogeneity in flooding disaster occurrence in the past 6 decades. The most recent decade reported highest number of disasters and greater spatial coverage as compared to the earlier decades. The data indicates that, in general, economic impacts of flooding disasters were notably higher in Pakistan, Afghanistan and Nepal. On the other hand, vulnerability scenarios with respect to human impacts were diverse for different countries. In terms of morbidity and mortality, Bangladesh, Pakistan, Bhutan and India were detected to be most susceptible to human impacts. Although Bhutan had seen lesser number of flooding disasters, higher population living within disaster prone region make them vulnerable. In summary, complex interactions between natural and socio-economic conditions play a dominant role to define and characterize the type and magnitude of vulnerability of HKH countries to disaster occurrence and their economic and human impacts.